2013
DOI: 10.1111/1556-4029.12259
|View full text |Cite
|
Sign up to set email alerts
|

A 21‐Locus Autosomal SNP Multiplex and its Application in Forensic Science

Abstract: To develop a cost-effective technique for single-nucleotide polymorphism (SNP) genotyping and improve the efficiency to analyze degraded DNA, we have established a novel multiplex system including 21-locus autosomal SNPs and amelogenin locus, which was based on allele-specific amplification (ASA) and universal reporter primers (URP). The target amplicons for each of the 21 SNPs arranged from 63 base pair (bp) to 192 bp. The system was tested in 539 samples from three ethnic groups (Han, Mongolian, and Zhuang p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In this study, 129 polymorphic universal SNPs from database of SNPforID [ 11 ] and IISNP [ 12 ] with MAF > 0.1 in Chinese Han [ 9 ] were included first. With published references of [ 13–20 ], 25 new SNPs with MAF > 0.3 in CHB or Asian population were found. Three SNPs (rs1029047, rs3808378 and rs1108414) of them were located within long homopolymers with sequence-checking and should be excluded from the panel.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, 129 polymorphic universal SNPs from database of SNPforID [ 11 ] and IISNP [ 12 ] with MAF > 0.1 in Chinese Han [ 9 ] were included first. With published references of [ 13–20 ], 25 new SNPs with MAF > 0.3 in CHB or Asian population were found. Three SNPs (rs1029047, rs3808378 and rs1108414) of them were located within long homopolymers with sequence-checking and should be excluded from the panel.…”
Section: Resultsmentioning
confidence: 99%
“…The newly developed panel we present here allows simultaneous sequencing of 231 SNPs chosen from SNPforID [ 11 ], IISNP [ 12 ], HapMap, dbSNP and published literatures [ 13–20 ] for forensic application. The library length ranges from 125 to 175 bp, which is suitable for sequencing of degraded DNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lou et al reported the performance of a 44 SNPs individual identification assay for Chinese based on an IISNP panel established by Pakstis et al [8,14]. There are other combinations of IISNPs for different Asian populations reported [18][19][20]. An IISNP panel for global forensic casework was established recently [21].…”
Section: Introductionmentioning
confidence: 99%